Antecedents of purchase intention in the use of online travel agents - Muhamad Yusup Alwi; Luki Adiati Pratomo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze whether there is a positive impact of information credibility, information quality, reviewer expertise, information quantity, product rating on the adoption of e-wom information, analyze whether there is a positive impact of e-wom information adoption on purchase intention, information from e-wom on attitude, information from e-wom on subjective norms, attitude on purchase intention, subjective norms on purchase intention. This research involves the use of the structural analysis method Equation Modeling (SEM) as a statistical tool to process research data, while data processing uses software tools, namely SPSS 21 and AMOS 23. The sampling technique used is purposive sampling. The expected results in this study can be concluded that there is a positive influence of information credibility on information adoption, information quality on information adoption, reviewer expertise on information adoption, information quantity on information adoption, product rating on information adoption, information adoption on purchase intention, information adoption on attitude, information adoption on subjective norms.